A study on correlation between workload and stress level among secondary school teachers / Oumsree Ananthakumarl - Oumsree, Ananthakumarl (2022)
Workload is the amount of work performed by someone usually within a specific time. In occupational safety and health settings, dealing with workload can be stressful and serve as a stressor for employees. Stress is felt as a pressure or burden often caused due to increase in workload, role conflict and not enough support from co-workers. Teaching career is a Nobel work but yet demanding career. Because of extended hours and heavy workloads, teachers are in danger of being overworked and not taking serious care about their own mental and physical health. The aimed of this research is to determine the correlation between workload and stress level among secondary school teachers. It is a cross-sectional study which use stratified sampling method to choose the schools. Workload is calculated using HSE Management Standards Indicator Tools questionnaire. Stress level calculated using International Stress Management Association United Kingdom (ISMAUK) questionnaire. Research result shows that, 55.0% of the teachers are having workload demand on sometimes and the stress level among school teachers are in medium level which is 50.0%. Moreover, the Pearson coefficient value shows 0.005, therefore there is significant correlation between workload and stress level among secondary school teachers. This reveals that the teaching profession is no more the profession of a little stress.